An Analysis of the COVID-19 Pandemic's Impact on the European Economy: A Multi-Dimensional Study - Desmond Cathal (Global Writing Academica Researching & Publishing, 2023)
The COVID-19 pandemic has had profound effects on global economies, with Europe being one of the most impacted regions. This study aims to analyze the economic impact of the COVID-19 pandemic in Europe, covering various sectors and considering the temporal progression of the pandemic. Using data from sources like Eurostat and OECD, coupled with econometric analysis, the study provides insights into how the pandemic has reshaped the economic landscape of Europe.